Masyarakat Tionghoa di Makassar dalam Pusaran Konflik Etnis 1965-1997 - Suardi Kaco. H Ardi; Musafir Pababari (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2023)
This article aims to reveal how and why the Tionghoa community in Makassar experienced prolonged ethnic conflict. The method used in this study is the method of writing history with a historical and sociological approach. In the results of the study it was found that the Tionghoa community in Makassar had been present since the 13th century. However, they were involved in the vortex of ethnic conflict since 1965-1997. This conflict resulted in inter-ethnic tensions and socio-economic losses for the Tionghoa community. Nonetheless, they continue to struggle to survive and contribute to the development of the City of Makassar. Their existence inspires the importance of tolerance and harmony in a multicultural society.